Epidemiology and mortality in bacterial bloodstream infections in patients with hematologic malignancies - Mert, Duygu; Ceken, Sabahat; Iskender, Gulsen; Iskender, Dicle; Merdin, Alparslan; Duygu, Fazilet; Ertek, Mustafa; Altuntas, Fevzi (The Journal of Infection in Developing Countries, 2019)
Introduction: Patients with hematological malignancies, who are in the high risk group for infectious complications and bacterial bloodstream infections. The aim of the study evaluated epidemiology and mortality in bacterial bloodstream infections in patients with hematologic malignancies. In addition to determine the risk factors, changes in the distribution and frequency of isolated bacterias. Methodology: In this retrospective study. There were investigated data from 266 patients with hematological malignancies and bacterial bloodstream infections who were hospitalized between the dates 01/01/2012 and 12/31/2017. Results: There were 305 blood and catheter cultures in febrile neutropenia attacks in total. In these total attacks, primary bloodstream infections were 166 and catheter-related bloodstream infections were 139. In blood cultures; Escherichia coli and Klebsiella pneumoniae bacteria were detected in 58,0% and 22,9% of the samples, respectively. 52,4% of the cultured Gram-negative bacterias were extended spectrum beta-lactamase (ESBL). Carbapenemase positive culture rate was 17,2% in Gram-negative bacteria cultures. Staphylococcus epidermidis was found in 38,4% of the Gram-positive bacteria cultures. In Gram-positive bacteria; methicillin resistance were detected in 82,2% of the samples. There was a statistically significant relationship between bloodstream infection and disease status. 60 patients with primary bloodstream infections were newly diagnosed. Conclusions: In patients with hematological malignancies, certain factors in the bloodstream infections increase the mortality rate. With the correction of these factors, the mortality rate in these patients can be reduced. The classification of such risk factors may be an important strategy to improve clinical decision making in high-risk patients, such as patients with hematological malignancies.